Aplikasi Eco-enzym untuk Pemurnian Air Terkontaminasi dan Budidaya Tanaman Obat Keluarga: Application of Eco-enzymes for Purification of Contaminated Water and Cultivation of Family Medicinal Plants - Probowati, Wiwit; Wijayanti, Suprihatin; Rika, Rika; Pramesti, Indah; Isnaini, Febriana Nur; Nisa, Neny Fahrun (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Increased water pollution due to industrial, household, and agricultural waste has triggered the need for environmentally friendly technologies for water purification. Eco-enzyme, a solution fermented from various kinds of fruit and vegetable kitchen waste with the addition of sugar and water is recognized to have anti-bacterial and anti-fungal properties effective in decomposing toxic substances and improving water quality. Utilization of waste enzymes is emerging as a viable strategy to treat contaminated water as well as organic fertilizer in the cultivation of family medicinal plants. This training activity on eco-enzyme making and pouring was carried out in the framework of community service activities and the 2024 eco-enzyme festival. Training on making eco-enzymes was carried out using socialization and demonstration methods. Then the finished eco-enzymes were poured into the river behind the campus of 'Aisyiyah University Yogyakarta and watered in the cultivation of Family Medicinal Plants in Sidoagung village, Godean sub-district, Sleman. Based on the evaluation of the activity, participants were very enthusiastic about understanding new knowledge and were able to practice the results of making eco-enzymes. In addition to creating a clean environment, pouring eco-enzymes into the river reduces the contamination of pollutants. In addition, the application of eco-enzymes to the cultivation of family medicinal plants can function as a liquid organic fertilizer that fertilizes the soil and optimizes plant growth.